A review on financial reporting laws in Malaysia: a comparison with the United States' Sarbanes-oxley Act 2002 / Siti Amirah Muhammad Ali … [et al.] - Muhammad Ali, Siti Amirah; Abdul Ghaffar, Nurul Afiqah; Amir Hamzah Maju, Nurulsakinah; Haron, Muhamad Firdaus (2013)
Financial reporting is said to be the pillar of good corporate governance. It is an important means of communication of the company to its shareholders and the public. However, several issues have arisen in sustaining good governance. The main issues discussed in this research paper are the transparency and disclosure in financial reporting by companies, and the roles of auditor in maintaining transparent disclosure in the preparation of financial reporting. A comparison had been made with the United States' Sarbanes-Oxley Act 2002 relating to the issues discussed. The aim of this research paper is to review Malaysian corporate laws governing disclosure and corporate fraud in the production of financial report.